The Effectiveness of Sport Massage and Swedish Massage in Reducing Fatigue Levels Among Mountain Climbers - Barokta Amiludin; Sri Sumartiningsih (Media Ilmu Keolahragaan Indonesia, 2025)
Abstract. Mountain climbing is a physically demanding activity requiring high levels of strength and endurance. After climbing activities, climbers frequently experience physical fatigue caused by lactic acid accumulation and prolonged energy expenditure. Effective recovery strategies are necessary to restore physiological conditions and improve post-activity recovery. Sport massage and Swedish massage are widely used recovery methods; however, comparative evidence regarding effectiveness in reducing fatigue among mountain climbers remains limited. The purpose of this study was to examine the differences in effectiveness between sport massage and Swedish massage in reducing fatigue levels among mountain climbers. A pretest–posttest experimental design was employed involving 30 participants selected through random sampling. Participants were divided into two groups consisting of 15 individuals in the sport massage group and 15 individuals in the Swedish massage group. Data were analyzed using paired t-tests and independent t-tests. The findings demonstrated that both sport massage and Swedish massage produced significant positive effects on reducing physical fatigue. Comparative analysis showed no statistically significant difference between both methods. However, sport massage demonstrated a higher effectiveness percentage (45%) compared with Swedish massage (35%). The novelty of the study lies in providing comparative evidence regarding massage-based recovery interventions specifically among mountain climbers. The findings contribute practical implications for selecting effective recovery strategies following physically demanding outdoor activities. Abstract in Indonesia. Mendaki gunung merupakan aktivitas fisik berat yang membutuhkan kekuatan dan daya tahan tubuh yang tinggi. Setelah aktivitas pendakian, pendaki sering mengalami kelelahan fisik akibat akumulasi asam laktat dan pengeluaran energi yang tinggi. Strategi pemulihan yang efektif diperlukan untuk mengembalikan kondisi fisiologis tubuh dan mempercepat proses pemulihan pascaaktivitas. Sport massage dan Swedish massage merupakan metode pemulihan yang sering digunakan, namun penelitian komparatif mengenai efektivitas kedua metode pada pendaki gunung masih terbatas. Penelitian ini bertujuan menganalisis perbedaan efektivitas sport massage dan Swedish massage dalam menurunkan tingkat kelelahan pada pendaki gunung. Penelitian menggunakan desain eksperimen pretest–posttest dengan jumlah sampel 30 orang yang dipilih menggunakan teknik random sampling. Partisipan dibagi menjadi dua kelompok, yaitu 15 orang kelompok sport massage dan 15 orang kelompok Swedish massage. Analisis data menggunakan paired t-test dan independent t-test. Hasil penelitian menunjukkan bahwa sport massage dan Swedish massage memberikan pengaruh positif yang signifikan terhadap penurunan kelelahan fisik. Analisis komparatif menunjukkan tidak terdapat perbedaan signifikan secara statistik antara kedua metode. Namun demikian, sport massage menunjukkan tingkat efektivitas lebih tinggi sebesar 45% dibandingkan Swedish massage sebesar 35%. Kebaruan penelitian terletak pada bukti komparatif intervensi pemulihan berbasis pijat yang secara khusus diterapkan pada pendaki gunung. Temuan penelitian memberikan implikasi praktis dalam pemilihan strategi pemulihan setelah aktivitas fisik berat.